Testate Amoeba Functional Traits and Their Use in Paleoecology - Marcisz, Katarzyna; Jassey, Vincent E. J.; Kosakyan, Anush; Krashevska, Valentyna; Lahr, Daniel J. G.; Lara, Enrique; Lamentowicz, Łukasz; Lamentowicz, Mariusz; Macumber, Andrew; Mazei, Yuri; Mitchell, Edward A. D.; Nasser, Nawaf A.; et al. (Frontiers in Ecology and Evolution, 2020)
This review provides a synthesis of current knowledge on the morphological and functional traits of testate amoebae, a polyphyletic group of protists commonly used as proxies of past hydrological changes in paleoecological investigations from peatland, lake sediment and soil archives. A trait-based approach to understanding testate amoebae ecology and paleoecology has gained in popularity in recent years, with research showing that morphological characteristics provide complementary information to the commonly used environmental inferences based on testate amoeba (morpho-)species data. We provide a broad overview of testate amoeba morphological and functional traits and trait-environment relationships in the context of ecology, evolution, genetics, biogeography, and paleoecology. As examples we report upon previous ecological and paleoecological studies that used trait-based approaches, and describe key testate amoebae traits that can be used to improve the interpretation of environmental studies. We also highlight knowledge gaps and speculate on potential future directions for the application of trait-based approaches in testate amoeba research.